Behavior of shear-critical prestressed concrete beams with recycled concrete aggregates under ultimate loads. (15th June 2018) - Brandes, Michael R.; Kurama, Yahya C.
Highlights: Shear behavior of prestressed beams with recycled concrete aggregates (RCA) was tested. RCA had relatively small effect on the overall ultimate shear behavior of the beams. Ability of methods to predict measured beam behavior was not significantly affected by RCA. Abstract: This paper investigates the effect of recycled concrete aggregates (RCA) on the ultimate-load behavior of shear-critical precast/prestressed concrete beams. A total of eighteen simply supported, normal strength concrete beam specimens were tested under four point bending with normalized moment-to-shear ratios of 2 and 1, defined as the distance from the simple support to the point of load application divided by the depth to the prestressing strands. Two sources of high-quality RCA (from rejected precast members and a construction demolition recycling yard) were used to replace natural crushed limestone at 50% and 100% by volume. Two different levels of prestressing were used. In general, the use of RCA had a relatively small effect (as compared with the high levels of aggregate replacement) on the overall ultimate load versus deflection behavior of the beams or on the progression of failure. Importantly, the ability of closed-form code design methods and nonlinear numerical models to predict the measured behaviors of the beams was not significantly affected by the aggregate replacement.